Isolation, Identification and Antimicrobial Susceptibility of some Bacterial Species Isolated from Dental Plaque - A. Mahdi, Mays; K. Raheem, Zahraa; F. Hamoodi, Hadeer; Jabbar Obaid, Ahmed (Al-Nahrain Journal of Science, 2024)
Dental plaque is a sticky bacterial film develops on teeth producing plaque as a result. If it ‘is not removed with regular dental cleanings and daily brushing, it can initiate oral health issues such as gum diseases and dental caries. This study aimed to determine the prevailing bacterial species found in some patient’s dental plaque cases dental caries and to analyze the antimicrobial susceptibility of obtained bacteria. A total of 60 samples of dental plaque were taken from patients who attended to the health centers in Baghdad with different ages using cotton swabs. All gained swabs were transported to the microbiology laboratory and cultured on culture media. According to standard laboratory diagnosis protocols, primary diagnosis was performed. VITE 2 Compact Automated- System (GP (and (GN (diagnosis cards used according to manufacturer company constructions (BioMérieux)to confirm the diagnosis. Antibiotic susceptibility test was done by using antibiotic disks according to Kirby- Bauer method. Out of 60 samples, forty-two (70%) samples showed growth on culture media, while 18 (30%) showed no growth, most of the isolates, 29 (69.0%) were Gram-positive bacteria represented by Streptococcus mutans, Staphylococcus aureus, and only 13 (30.9%) of isolates were Gram-negative includes Klebsiella pneumoniae and Escherichia coli.  According to the antibiotic susceptibility test results, Gram-positive bacteria showed high resistance against amoxicillin, Cefotaxim and erythromycin with percentages of 86.2%- and 89.6% respectively. Gram-negative bacteria showed high resistance against amoxicillin and erythromycin with percentage of 76.9% and 69.2% against Cefotaxim.